2013
DOI: 10.4236/ojped.2013.34061
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV/AIDS on mortality and nutritional recovery among hospitalized severely malnourished children before starting antiretroviral treatment

Abstract: In low income countries, severe acute malnutrition remains a major problem for HIV-infected children and an important risk factor for mortality. This study aims to analyze HIV impact on mortality rate and nutritional recovery among severely malnourished HIV/AIDS uninfected and infected children. This was a retrospective cohort study conducted from data of 521 hospitalized severely malnourished children. We used Pearson's Chi square test to compare proportions; and Student's independent t-test to compare means;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
6
10
1
Order By: Relevance
“…This is often driven by economic factors, and we are not aware of processes which might lead to selective or biased ascertainment of death in HIV infected or uninfected children. The hazard ratio of HIV for mortality in our programme was 5.2 which is consistent with, but slightly higher than, hazard ratios for death of 2.0 in Malawi [ 24 ], 3.7 in Burkina Faso [ 25 ], or 4.0 in another study from Malawi [ 14 ]. Defaulter rates were generally high and mainly in HIV exposed and infected children, whose caretakers often fail to disclose their status to the spouse for fear of being divorced and may choose to drop out of the programme.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is often driven by economic factors, and we are not aware of processes which might lead to selective or biased ascertainment of death in HIV infected or uninfected children. The hazard ratio of HIV for mortality in our programme was 5.2 which is consistent with, but slightly higher than, hazard ratios for death of 2.0 in Malawi [ 24 ], 3.7 in Burkina Faso [ 25 ], or 4.0 in another study from Malawi [ 14 ]. Defaulter rates were generally high and mainly in HIV exposed and infected children, whose caretakers often fail to disclose their status to the spouse for fear of being divorced and may choose to drop out of the programme.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings therefore cannot mandate a change of strategy, but there are several reasons to encourage integration of HIV care into CMAM in heavily affected countries. First, hospital-based studies consistently demonstrate that HIV increases mortality in childhood malnutrition [ 14 , 25 ]. Second, screening for malnutrition offers an excellent opportunity to screen for HIV in heavily affected communities, and these children then need treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The results were similar in both hospitals. Savadogo et al [22] also found similar relationships between HIV status and the RWG; however, unlike in the present study, they used the median RWG as a measure of the distribution of the RWG by HIV status. Their results revealed that HIV-positive SAM patients achieved a median of 4.64 g/kg/day v. 9.04 g/kg/day for HIV-negative patients.…”
Section: Discussionsupporting
confidence: 50%
“…These estimates were slightly higher than those recently reported in Burkina Faso (39.7% v. 10.9% for HIV-infected and HIV-uninfected cases, respectively). [17] A study in Niger also reported the same direction of relationship but with much lower CFRs for HIV-infected and HIVuninfected SAM cases (20% and 14%, respectively). [18] In this study we have shown that disease severity at baseline was independently associated with excess mortality, a finding that is consistent with past evidence by Maitland et al [14] Children with SAM who were admitted with one or a combination of clinical features such as coma, hypoglycaemia, hypothermia and bradycardia, had the worst survival probability compared with those who had other less SAM-related manifestations, such as herbal intoxication, Cushingoid facies, etc.…”
Section: Discussionmentioning
confidence: 73%
“…[19] However, some authors continue to attribute excess mortality to complex pathophysiological, metabolic and pharmacological changes that occur as HIV infection progresses. [17] HIV-infected SAM patients in the current study were initiated on ART using the standard guidelines. However, the timing of ART in preventing premature mortality among HIV-infected SAM cases at different disease stages remains a challenge.…”
Section: Discussionmentioning
confidence: 99%